2018
DOI: 10.1002/celc.201800588
|View full text |Cite
|
Sign up to set email alerts
|

High Performance Electrocatalyst Based on MIL‐101(Cr)/Reduced Graphene Oxide Composite: Facile Synthesis and Electrochemical Detections

Abstract: In this work, a Cr-based MOF (MIL-101(Cr))/reduced grapheme oxide(rGO) electrocatalyst was prepared through a one-pot hydrothermal method. The obtained composite was characterized via scanning electron microscopy, transmission electron microscopy, X-ray diffraction and other standard techniques. Electrochemical methods were adopted to study the electrocatalytic ability of the composite. The results imply that, compared to the single components, it exhibits higher electrocatalytic activity for the reduction of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 68 publications
0
9
0
Order By: Relevance
“…For example, Ma and coworkers found that the electrochemically active polyaniline polymerized in the pores of UiO‐66‐NH 2 can exhibit a much better electrochemical activity for the detection of cadmium ions compared to both the pristine polyaniline and UiO‐66‐NH 2 (Figure (c)) . In addition to Zr‐MOFs, MIL‐101(Cr) was also chosen to prepare the MOF‐based composite with reduced graphene oxide, and the resulting composite can be applied for electrochemical detections of cadmium and lead ions . Table lists the selected studies on MOF‐based materials for electrochemical sensing applications published recently.…”
Section: Charge Transport In Mofsmentioning
confidence: 99%
“…For example, Ma and coworkers found that the electrochemically active polyaniline polymerized in the pores of UiO‐66‐NH 2 can exhibit a much better electrochemical activity for the detection of cadmium ions compared to both the pristine polyaniline and UiO‐66‐NH 2 (Figure (c)) . In addition to Zr‐MOFs, MIL‐101(Cr) was also chosen to prepare the MOF‐based composite with reduced graphene oxide, and the resulting composite can be applied for electrochemical detections of cadmium and lead ions . Table lists the selected studies on MOF‐based materials for electrochemical sensing applications published recently.…”
Section: Charge Transport In Mofsmentioning
confidence: 99%
“…In Fig. 1A, MIL-101 (Cr) exhibited a typical octahedral structure, and the diameter of particles was between 400 and 600 nm [16,22]. The TEM image of MIL-101 (Cr) is shown in Fig.…”
Section: Physical Characterizations and Optical Propertymentioning
confidence: 95%
“…For example, Cao et al used Cu-BTC MOF/g-C 3 N 4 to prepare a glyphosate photo-electrochemical sensor for the detection of glyphosate [15]. Gu et al used reduced graphene oxide combined with Cr-MOF to enhance the electro-catalytic activity of MOF for the detection of heavy metal ions [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MOF materials have the advantages of large specific surface area, many adsorbable sites, strong designability, and functional modification [ 103 , 104 , 105 ]. They are used in the fields of chemical sensing [ 106 ], electrochemical detection [ 107 ], catalysis [ 108 ], gas adsorption and separation [ 109 ], and drug loading [ 110 ]. Continuous progress has been made and has received widespread attention in recent decades.…”
Section: Construction Of Porphyrin-based Materials For Metal Ions mentioning
confidence: 99%